In Vitro and In Vivo Analysis of Extracellular Vesicle‐Mediated Metastasis Using a Bright, Red‐Shifted Bioluminescent Reporter Protein (Advanced Genetics 1/03). Issue 1 (18th March 2022) - Perez, Gloria I.; Broadbent, David; Zarea, Ahmed A.; Dolgikh, Benedikt; Bernard, Matthew P.; Withrow, Alicia; McGill, Amelia; Toomajian, Victoria; Thampy, Lukose K.; Harkema, Jack; Walker, Joel R.; Kirkland, Thomas A.; et al.
Abstract : Extracellular Vesicle Imaging Cancer cell‐derived extracellular vesicles (EVs) promote tumor growth and spread. Studying the distribution of EVs in the body is key to understanding cancer progression and developing therapies. In article number 2100055, Masamitsu Kanada and co‐workers develop a highly sensitive EV reporter for tracking heterogeneous EV populations released from cancer cells in live mice.